Exploring the impact of surgical treatment for lung cancer in patients with Airway Obstruction from a Lung Cancer Screening Program - Juan P. de-Torres; Juan José Girón-Flamenco; María Rodríguez; Alejandra de la Fuente-Añó; Valerio Perna; Miguel Mesa-Guzmán; Diego Murillo; Ana Belén Alcaide; Arancha Campo; Javier J. Zulueta; Gorka Bastarrika; Ana Ezponda; et al. (PLoS ONE, 2025)
Introduction Little information is available on the surgical treatment options for patients with Airway Obstruction (AO) and early-stage non-small cell lung cancer (NSCLC) followed in lung cancer screening programs (LCS). This study aims to compare the potential impact of anatomical sub lobar resections vs. lobectomies in these patients. Methods This is a retrospective analysis of participants who underwent surgical resections within a Lung Cancer Screening Program, including those with AO (post bronchodilator FEV1/FVC < 0.70). The short-term survival, locoregional recurrence, perioperative complications, and difference between pre and postoperative pulmonary function tests were compared between the surgical groups in those with AO. Results Anatomical sub lobar resections or lobectomies for Stages IA and IB NSCLC were performed in 133 patients. Out of these, 57 had AO. Anatomical sub lobar resections were non-inferior to lobectomies for short-term survival in patients with AO (3-year survival rate: 95.8% vs. 97%, p = 0.83). In these patients, sub lobar resections had a higher recurrence rate (12.5% vs 0%, p < 0.01). No significant differences were found in postoperative complications between surgical techniques (sub lobar 33% vs lobectomy 24%, p = 0.44). Lastly, no significant difference was found on the change between pre and postoperative FEV1 and DLCO (p = 0.96 and 0.79 for FEV1 and DLCO, respectively). Conclusions The present retrospective analysis suggests that sub lobar resection might be the best surgical option for treating early-stage NSCLC in patients with AO, where lung function preservation techniques are desired, but requires closer follow up to detect recurrence. Further studies in larger samples should confirm our findings.